2022
DOI: 10.3390/ijms23136945
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Status of the Intestinal and Hepatic Cells after Short Term Exposure to Fumonisin B1 and Aflatoxin B1

Abstract: Fumonisin B1 (FB1) and aflatoxin B1 (AFB1) are frequent contaminants of staple foods such as maize. Oral exposure to these toxins poses health hazards by disrupting cellular signaling. However, little is known regarding the multifaced mitochondrial dysfunction-linked toxicity of FB1 and AFB1. Here, we show that after exposure to FB1 and AFB1, mitochondrial respiration significantly decreased by measuring the oxygen consumption rate (OCR), mitochondrial membrane potential (MMP) and reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…37,41 It has also been reported that AFB1 disrupts the integrity of the mitochondria (MMP and ROS), inducing mitochondrial dysfunction and impairing mitochondrial respiration in undifferentiated Caco-2 cells, an in vitro model of the human intestine. 42 In the present study, co-exposure to ZEN, DON, and AFB1 caused mitochondrial damage, accompanied by the disruption of the mitochondrial morphological dynamics indicated by increase of mitochondrial fission and reduction of mitochondrial fusion. LYC is a common dietary supplement with antioxidant properties that also modulates the homeostasis of mitochondrial lipids.…”
Section: Discussionsupporting
confidence: 47%
“…37,41 It has also been reported that AFB1 disrupts the integrity of the mitochondria (MMP and ROS), inducing mitochondrial dysfunction and impairing mitochondrial respiration in undifferentiated Caco-2 cells, an in vitro model of the human intestine. 42 In the present study, co-exposure to ZEN, DON, and AFB1 caused mitochondrial damage, accompanied by the disruption of the mitochondrial morphological dynamics indicated by increase of mitochondrial fission and reduction of mitochondrial fusion. LYC is a common dietary supplement with antioxidant properties that also modulates the homeostasis of mitochondrial lipids.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, we applied three combinations (low-low, middle-middle, and high-high) as a binary mixture (MIX) of AFB1 and FB1 ( Table 1 ). These concentrations were applied based on the estimated exposure data derived from measuring the average of urinary biomarkers of AFB1 (0.5 µg/mL) and FB1(10 µg/mL) in humans, which were considered here in the current work as low exposure scenario (Chen et al 2022; Meneely et al 2018). This level was increased four folds to have a middle exposure scenario and eight folds as high exposure scenario to investigate the potential toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…The tetrazolium salt (MTT) (Life Technologies Corporation, Eugene, OR, USA) assay, which is based on the cellular conversion of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide into formazan, was performed to determine the cell viability after the exposure to AFB1 and FB1 (Chen et al 2022). Briefly, HepG2 cells were seeded before the treatment in 96-well plates at a density of 20,000 per well for 24 h at 37 ⍰ in a sterilized incubator with a humidified atmosphere of 10 % CO 2 to allow cell adhesion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations